1ST International Congress on Research, Technological Development and Innovation in University Education - Gerber Sergio Pérez Postigo; Beatriz Amante García; María Martínez Martínez (OmniaScience, 2023)
Different papers have been presented to the congress by renowned researchers along the following five thematic lines: - Scientific research, training and researcher training - Research, innovation and development policies in Higher Education. - Paradigms in scientific research and new epistemological challenges in the production of knowledge in Latin American universities. - Internationalization of research networks, groups and institutes. - Public communication of science and technology.